2023
DOI: 10.1177/17588359231210271
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal duration, dose and frequency for anti-PD1 therapy of non-small cell lung cancer?

Chii Yang Kuah,
Robert Monfries,
Matteo Quartagno
et al.

Abstract: Over the past decade, immune checkpoint inhibitors (ICIs) have transformed the management of multiple malignancies including lung cancer. However, the optimal use of these agents in terms of duration, dose and administration frequency remains unknown. Focusing on anti-PD1 agents nivolumab and pembrolizumab in the context of non-small cell lung cancer, we argue that several lines of evidence suggest current administration regimens of these drugs may result in overtreatment with potentially important implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…PD-1 antibody significantly increased the level of IFN-g, granzyme-B, and a proliferation marker of T-cell that is Ki-67; the CAR-T cell combined with anti PD-1 showed significantly higher anti-tumor response compared to only CAR-T cells and isotype control antibody (123). However, the optimal doses and frequencies of administration of anti PD-1 may not be generalized as different targets for immunotherapy and different agents show different dose response characteristics (124). Thus, in the case of cell extrinsic combination therapy, the doses of PD-1 blocking agents vary based on tumor type and grading, and there may be a need for repeated administration of anti PD-1 antibodies at a regular interval.…”
Section: Cell Extrinsic Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…PD-1 antibody significantly increased the level of IFN-g, granzyme-B, and a proliferation marker of T-cell that is Ki-67; the CAR-T cell combined with anti PD-1 showed significantly higher anti-tumor response compared to only CAR-T cells and isotype control antibody (123). However, the optimal doses and frequencies of administration of anti PD-1 may not be generalized as different targets for immunotherapy and different agents show different dose response characteristics (124). Thus, in the case of cell extrinsic combination therapy, the doses of PD-1 blocking agents vary based on tumor type and grading, and there may be a need for repeated administration of anti PD-1 antibodies at a regular interval.…”
Section: Cell Extrinsic Combination Therapymentioning
confidence: 99%
“…Although extrinsic combination therapy shows promising results, there are some drawbacks associated with it. Kuah et al (2023) suggested optimizing the doses of anti PD-1 drugs as current administration regimens may result in overtreatment with potentially important implications for cost, quality of life, and toxicity (124).…”
Section: Cell Extrinsic Combination Therapymentioning
confidence: 99%
“…The huge steps made in other malignancies such as melanoma and lung cancer with regard to checkpoint immunotherapies including PD-1 targeting agents begged the question as to whether similar success might be seen in GTN in the rare situation that standard chemotherapy is not effective [8]. The discovery that PDL1 inhibition was beneficial in 3 out of 4 patients who had failed existing therapies and were expected to die has led to a revolution in the treatment of GTN.…”
mentioning
confidence: 99%